Clinical implications and prognostic role of minimal residual disease detection in follicular lymphoma. (June 2013) - Lobetti-Bodoni, Chiara; Mantoan, Barbara; Monitillo, Luigia; Genuardi, Elisa; Drandi, Daniela; Barbero, Daniela; Bernocco, Elisa; Boccadoro, Mario; Ladetto, Marco
The identification of patients at high risk of relapse is a critical goal of modern translational research in oncohematology. Minimal residual disease (MRD) detection by polymerase chain reaction-based methods is routinely employed in the management of patients with acute lymphoblastic leukemia. Current knowledge indicates that it is also a useful prognostic tool in several mature lymphoproliferative disorders and particularly in follicular lymphoma (FL). Based on this evidence clinical trials employing MRD-based risk stratification are currently ongoing in FL. In this review the 'state of the art' of MRD evaluation in FL is discussed. A short description of technical issues and recent methodological advances is provided. Then, the bulk of the review focuses on critical take-home messages for clinicians working in the field. Finally, we discuss future perspectives of MRD detection and more generally outcome prediction in FL.